“Calming the nightmares”: A qualitative study of a socially assistive robot for sensory and emotional support in individuals with eating disorders and PTSD - Dimitri Chubinidze; Zhuo Li; Philippa Croft; Brittany Nodding; Petr Slovak; Kate Tchanturia (PLoS ONE, 2025)
Individuals with eating disorders (ED) and co-occurring post-traumatic stress disorder (PTSD) often face difficulties with sensory overload and emotion regulation (ER), which can make treatment more complex. Assistive devices that offer real-time support are needed to enhance therapeutic interventions. This qualitative pilot study explored the engagement, acceptability, and perceived impact of Purrble, a socially assistive robot, as an adjunct tool for sensory and ER support. Nine participants (8 female, 1 non-binary, aged 20–55) were recruited from an ED service and engaged with Purrble over a 10-day period following a sensory well-being workshop. Participants recorded their use of Purrble and daily reflections in diaries and participated in a focus group. Thematic analysis revealed three themes: (1) Integration into daily life, where participants highlighted Purrble’s portability and ease of use in managing anxiety across various settings; (2) Managing PTSD-related difficulties, such as calming nightmares, reducing sensory overload, and providing emotional comfort; and (3) Challenges and improvements, where participants suggested modifications, such as adding a night mode and better sound control. This study provides preliminary evidence that an assistive device can support individuals with ED and PTSD, particularly in managing sleep disturbances, overstimulation, and feelings of emotional isolation. Further research using standardised methodologies is needed to expand on these preliminary findings.